National Inpatient Datasets May No Longer Be Appropriate for Overall Total Hip and Knee Arthroplasties Projections after Removal from Inpatient-Only Lists - Rullán, Pedro J.; Emara, Ahmed K.; Zhou, Guangjin; Pasqualini, Ignacio; Klika, Alison K.; Koroukian, Siran; Barsoum, Wael K.; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2023)
It is unknown if the National Inpatient Sample (NIS) remains suitable to conduct projections for total knee arthroplasty (TKA) and total hip arthroplasty (THA), after their removal from “inpatient-only lists” in 2018 and 2020, respectively. We aimed to: (1) quantify primary THA and TKA volume from 2008 to 2018; (2) project estimates of future volume of THA and TKA until 2050; and (3) compare projections based on NIS data from 2008 to 2018 and 2008 to 2017, respectively. We identified all primary THA and TKA performed from 2008 to 2018 from the NIS. The projected volumes of THA and TKA were modeled using negative binomial regression models while incorporating log-transformed population data from the Centers for Disease Control and Prevention. Annual volume increased by 26% for THA and 11% for TKA (2008/2018: THA: 360,891/465,559; TKA:592,352/657,294). Based on 2008 to 2018 data, THA volume is projected to grow 120%, to 1,119,942 THAs by 2050. While, based on 2008 to 2017 data, THA volume is projected to grow 136%, to 1,219,852 THAs by 2050. Based on 2008 to 2018 data, TKA volume is projected to grow 4%, to 794,852 TKAs by 2050. While, based on 2008 to 2017 data, TKA volume is projected to grow 28%, to 1,037,474 TKAs by 2050. Projections based on 2008 to 2017 data estimated up to 240,000 (23%) more annual TKAs by 2050, compared with projections based on 2008 to 2018 data. The largest discrepancy among THA projections was an 8.2% difference (99,000 THAs) for 2050. After 2018 for TKA, and potentially 2020 for THA, projections based on the NIS will have to be interpreted with caution and may only be appropriate to estimate future inpatient volume. Level of evidence is prognostic level II.
Keywords: THA; TKA; surgical volume; nationwide utilization; outpatient; shift